Nanocellulose-Based Scaffolds for Chondrogenic Differentiation and Expansion - Szustak, Marcin; Gendaszewska-Darmach, Edyta (Frontiers in Bioengineering and Biotechnology, 2021)
Nanocellulose deserves special attention among the large group of biocompatible biomaterials. It exhibits good mechanical properties, which qualifies it for potential use as a scaffold imitating cartilage. However, the reconstruction of cartilage is a big challenge due to this tissue's limited regenerative capacity resulting from its lack of vascularization, innervations, and sparsely distributed chondrocytes. This feature restricts the infiltration of progenitor cells into damaged sites. Unfortunately, differentiated chondrocytes are challenging to obtain, and mesenchymal stem cells have become an alternative approach to promote chondrogenesis. Importantly, nanocellulose scaffolds induce the differentiation of stem cells into chondrocyte phenotypes. In this review, we present the recent progress of nanocellulose-based scaffolds promoting the development of cartilage tissue, especially within the emphasis on chondrogenic differentiation and expansion.